Rhabdomyolysis in a neonate due to very long chain acyl CoA dehydrogenase deficiency - Jessica Scott Schwoerer; Gena Cooper; Sandra van Calcar (Molecular Genetics and Metabolism Reports, 2015)
Very long chain acyl CoA dehydrogenase deficiency (VLCADD) is an inborn error in long chain fatty acid oxidation with significant variability in the severity and timing of its clinical presentation. Neonatal presentations of VLCADD have included hypoglycemia and cardiomyopathy while rhabdomyolysis is usually a later onset complication. We describe a neonate with VLCADD presenting with rhabdomyolysis prior to the return of an abnormal newborn screen. This report suggests that evaluating for rhabdomyolysis, in addition to a cardiac and hepatic work-up, is an important part of the initial evaluation of an infant with an abnormal newborn screen suggesting a diagnosis of VLCADD.